2020
DOI: 10.1038/s41598-020-57877-z
|View full text |Cite
|
Sign up to set email alerts
|

Implications of C1q/TNF-related protein superfamily in patients with coronary artery disease

Abstract: The C1q complement/TNF-related protein superfamily (CTRPs) displays differential effects on the regulation of metabolic homeostasis, governing cardiovascular function. However, whether and how they may serve as predictor/pro-diagnosis factors for assessing the risks of coronary artery disease (CAD) remains controversial. Therefore, we performed a clinical study to elaborate on the implication of CTRPs (CTRP1, CTRP5, CTRP7, and CTRP15) in CAD. CTRP1 were significantly increased, whereas CTRP7 and CTRP15 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Serum myonectin was correlated with disease severity of CAD. Zhang reported that serum myonectin levels were decreased in CAD patients compared to the non-CAD group 12 . Serum myonectin alteration may serve as a marker for CAD 12 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Serum myonectin was correlated with disease severity of CAD. Zhang reported that serum myonectin levels were decreased in CAD patients compared to the non-CAD group 12 . Serum myonectin alteration may serve as a marker for CAD 12 .…”
Section: Discussionmentioning
confidence: 98%
“…Zhang reported that serum myonectin levels were decreased in CAD patients compared to the non-CAD group 12 . Serum myonectin alteration may serve as a marker for CAD 12 . Myonectin-knockout mice with ischemia–reperfusion showed the enhancement of myocardial infarct size, cardiac dysfunction, apoptosis, and proinflammatory gene expression compared with wild-type mice 6 .…”
Section: Discussionmentioning
confidence: 98%
“…Similar to our results, a small sample study in obese individuals (n = 37) showed that the level of serum CTRP7 in obese individuals was significantly increased and positively correlated with BMI, glucose, insulin, and HOMA-IR ( 11 ). In addition, one study reported decreased circulating CTRP7 levels in coronary artery disease (CAD) patients and may serve as a biomarker of CAD ( 37 ). Another study revealed that the production of CTRP7 in muscle tissue was increased and further increased by caloric restriction in old animals ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic cardiac disease is a type of disease given to heart problems caused by narrowed heart arteries that lead to myocardiac ischemia (MI). A variety of links have been made between CTRPs and ischemic cardiac disease [ 58 ]. The involved mechanisms has been clarified in many aspects.…”
Section: Ctrps and Cardiac Diseasesmentioning
confidence: 99%